Dynamics of in vivo ASC speck formation - Kuri Rodríguez, Paola Sofía; Thumberger, Thomas; Wittbrodt, Joachim (The journal of cell biology, 2017)
Activated danger or pathogen sensors trigger assembly of the inflammasome adaptor ASC into specks, large signaling platforms considered hallmarks of inflammasome activation. Because a lack of in vivo tools has prevented the study of endogenous ASC dynamics, we generated a live ASC reporter through CRISPR/Cas9 tagging of the endogenous gene in zebrafish. We see strong ASC expression in the skin and other epithelia that act as barriers to insult. A toxic stimulus triggered speck formation and rapid pyroptosis in keratinocytes in vivo. Macrophages engulfed and digested that speck-containing, pyroptotic debris. A three-dimensional, ultrastructural reconstruction, based on correlative light and electron microscopy of the in vivo assembled specks revealed a compact network of highly intercrossed filaments, whereas pyrin domain (PYD) or caspase activation and recruitment domain alone formed filamentous aggregates. The effector caspase is recruited through PYD, whose overexpression induced pyroptosis but only after substantial delay. Therefore, formation of a single, compact speck and rapid cell-death induction in vivo requires a full-length ASC.
Gesehen am 12.09.2018